PROCESSING OF STEEL 110G13L WITH BARIUMSTRONTIUM CARBONATES - V. A. Rozum; S. P. Zadrutskij; A. P. Bezhok; I. I. Baeshko; G. P. Goretskij; R. N. Chajchits; V. S. Gajkevich (Литьë и металлургия, 2010)
It is shown that modification of steel with bariumstrontium carbonates promotes grinding of carbide impurities and decrease of their quantity in cast condition.